Identifikasi Komponen Kimia Ekstrak Daun Ketapang (Terminalia cattapa) Berdasarkan Perbandingan Metode Ekstraksi - Marzuki, Ismail; Mirsyah, Melisa; Gala, Selfina (Al-Kimia, 2022)
Screening, characterization and identification of chemical components of typical Indonesian plants are important for the purpose of finding high potential chemical components in the use of primary sources of cosmetic, medicinal and food ingredients. The selection of the right extraction method and the appropriate type of solvent is very decisive in the acquisition of the target chemical components. The brand of this research focuses on the comparison of extraction between soxhletation and maceration methods in identifying the chemical components of Ketapang leaves (Terminalia Catappa). Sample preparation was carried out by selecting fresh, cleaned, dried and mashed Ketapang leaves. The extraction was carried out in two stages using two types of solvents, namely the first stage of extraction using ethanol. Obtained a dilute extract, then concentrated using a rotary evaporator. The second extraction used n-hexane as solvent. There are 4 kinds of extracts, each ethanol extract and n-hexane extract by applying the soxhletation and maceration method. The results obtained showed that: the application of the maceration method to the identification of chemical components of ketapang leaves gave relatively better separation results than the soxhletation method. The number of chemical components identified from the ethanol extract of ketapang leaves is ± 20 species which are dominated by fatty acid compounds. There are two groups of chemical compounds identified from ketapang leaves using n-hexane as solvent both in the application of soxhletation and maceration methods with high similarity 90%, namely 4 kinds of chemical components of the fatty acid group (tetradecanoic acid, Hexadecanoic, Octadecanoid, Octadeca-9,12 -Dienoite) and 2 kinds of aliphatic components (methyl cyclopentane, Tetraco Hexane)